Hypomethylation of miR-142 promoter and upregulation of microRNAs that target the oxytocin receptor gene in the autism prefrontal cortex - Mor, Michal (Mol Autism, 2015)
BACKGROUND: MicroRNAs are small RNA molecules that regulate the translation of protein from gene transcripts and are a powerful mechanism to regulate gene networks. Next-generation sequencing technologies have produced important insights into gene transcription changes that occur in the brain of individuals diagnosed with autism spectrum disorder (asd). However, these technologies have not yet been employed to uncover changes in microRNAs in the brain of individuals diagnosed with asd. METHODS: Small RNA next-generation sequencing was performed on RNA extracted from 12 human autism brain samples and 12 controls. Real-time PCR was used to validate a sample of the differentially expressed microRNAs, and bioinformatic analysis determined common pathways of gene targets. MicroRNA expression data was correlated to genome-wide DNA methylation data to determine if there is epigenetic regulation of dysregulated microRNAs in the autism brain. Luciferase assays, real-time PCR, and Western blot analysis were used to determine how dysregulated microRNAs may regulate the expression and translation of an autism-related gene transcript. RESULTS: We determined that miR-142-5p, miR-142-3p, miR-451a, miR-144-3p, and miR-21-5p are overexpressed in the asd brain. Furthermore, the promoter region of the miR-142 gene is hypomethylated in the same brain samples, suggesting that epigenetics plays a role in dysregulation of microRNAs in the brain. Bioinformatic analysis revealed that these microRNAs target genes that are involved in synaptic function. Further bioinformatic analysis, coupled with in vitro luciferase assays, determined that miR-451a and miR-21-5p can target the oxytocin receptor (OXTR) gene. OXTR gene expression is increased in these same brain samples, and there is a positive correlation between miR-21-5p and OXTR expression. However, miR-21-5p expression negatively correlates to production of OXTR protein from the OXTR transcript. Therefore, we suggest that miR-21-5p may attenuate OXTR expression in the human autism brain. CONCLUSIONS: Our data suggests that dysregulation of microRNAs may play a biological role in the brain of individuals of autism. In addition, we suggest an interaction between epigenetic mechanisms and microRNA dysregulation in the brain. Overall, this data adds an important link in our understanding of the molecular events that are dysregulated in the brain of individuals diagnosed with autism. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13229-015-0040-1) contains supplementary material, which is available to authorized users.